Comparison of extractive content between stem and branch of kenaf (Hibiscus cannibinus) / Mohd Hisham Baharom - Baharom, Mohd Hisham (2005)
Kenaf or (Hibiscus cannibinus) spp was studied for chemical analysis as the main material taken at part of stem and branch. This experiment was carried out to determine the variation of extraneous component in this species. Two experiments were carried out in the laboratory namely determination of hot water soluble and determination of alcohol benzene soluble. Finding from the study indicated that both the hot water soluble and alcohol-benzene soluble were higher in term of percentage at the stem portion when compared to the branch portion. Thus, stem of kenaf possesses higher extractives than the branch portion. This therefore several an indicator for find and use leading to more effective utilization of kenaf tree.